Market strategies for Central American dry beans. - Mertínez, Lourdes (2004)
In the past few years, the dry bean sub-sector in CentralAmerica has witnessed many dynamic changes. Unless wefind ways to increase the competitiveness of the regionalbean sub-sector, Central American countries will likelyexperience significant negative social and economic impacts,especially since these countries are facing the challenge ofadjusting to new open markets, such as the Central AmericanFree Trade Agreement (CAFTA). Bean traders, retailers, andknowledgeable government official in Costa Rica, ElSalvador, Honduras, Guatemala, and Nicaragua wereinterviewed to document these changes, identify constraintsthat threaten the viability of the sub-sector, and assess futureopportunities for increasing bean market shares. The resultsindicate that to remain competitive in the future, CentralAmerican countries must increase productivity by continuingto support dry bean research (i.e., develop improved varietieswith characteristics that consumers prefer such as graincolor); strengthen programs for distributing improvedvarieties to producers; provide producers with better marketinformation; develop stronger linkages between producers,packers, wholesalers, and supermarkets; and aggressivelytarget the U.S. export market.